Outcomes of In-Hospital Cardiopulmonary Resuscitation after Introduction of Medical Emergency Team - Gulacti, Umut; Lok, Ugur; Aydin, Irfan; Gurger, Mehtap; Hatipoglu, Sinan; Polat, Haci (Kuwait Medical Assoc, 2016)
Objective: Many countries set up clinical emergency response systems such as medical emergency team, rapid response team. But there are still some problems regarding the benefit, design, and advisability of implementing a clinical emergency response system. The present study evaluated the outcomes of in-hospital cardiopulmonary resuscitation after introduction of the first comprehensive the code blue and medical emergency team (MET) system on cardiopulmonary resuscitation (CPR) attempts in-hospital. Design: Retrospective study Setting: Harput State Hospital, Department of Emergency Medicine, Elazig, Turkey Subjects: All code blue calls applied in this hospital from January 2010 to June 2011 were evaluated Intervention: None Main outcome measures: Rates of return of spontaneous circulation (ROSC) and survival to hospital discharge after CPR Results: A total of 264 code blue calls were performed during study period. There were 186 (70.5%) calls required immediately CPR attempt, 50 (18.9%) calls required only medical treatments, 18 (6.8%) drill calls for code blue team and 10 (3.7%) missed calls. ROSC and survival to hospital discharge were 41.4% and 6.4% respectively. Time of arrival at the scene was less than two minutes in 74.7% of code blue calls. ROSC occurred in 88.2% of VT/VF cases. A duration of CPR of less than 15 min was related to better CPR outcomes and ROSC (p <0.001). Conclusion: Response to CPR attempts is affected by early activation of the code blue system and early response of the MET. Therefore, introduction of MET and code blue systems is required for all hospitals in the world.
Keywords: cardiac arrest; code blue; emergency intervention; intensive care; medical emergency